2012
DOI: 10.2478/v10289-012-0023-9
|View full text |Cite
|
Sign up to set email alerts
|

Nectar of Ziziphus spina-christi (L.) Willd (Rhamnaceae): Dynamics of Secretion and Potential for Honey Production

Abstract: The nectar secretion of Ziziphus flowers was studied by removing and measuring the nectar every four hours, for two consecutive days, from 88 flowers of four trees (‘repeated sampling’). In another 120 flowers from the same trees, the accumulated sugar was measured at the end of the flowering stage. The mass of the nectar sugar was determined following the washing technique. The total amount of sugar per tree was calculated by multiplying the number of flowers per tree by the average mass of nectar sugar secre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 16 publications
(13 reference statements)
2
14
0
Order By: Relevance
“…It is a massive flowering plant and is commonly found at altitudes ranging from 0 to 2000 m a.s.l. [31] Similar findings for Ziziphus honey pollen types have been previously reported by Al-Khalifa and Al-Arify. [32] They reported that the floral source of Asir Ziziphus honey is Z. spina-christi.…”
Section: Floral Originsupporting
confidence: 84%
“…It is a massive flowering plant and is commonly found at altitudes ranging from 0 to 2000 m a.s.l. [31] Similar findings for Ziziphus honey pollen types have been previously reported by Al-Khalifa and Al-Arify. [32] They reported that the floral source of Asir Ziziphus honey is Z. spina-christi.…”
Section: Floral Originsupporting
confidence: 84%
“…The positive correlations between the amount of nectar and the air temperature of the area might indicate the adaptation of these species to warm climatic conditions. Similarly, positive correlations between ambient temperature and the Brought to you by | MIT Libraries Authenticated Download Date | 5/12/18 3:09 AM nectar secretion amount, have been recorded for numerous nectar-secreting species e.g., Trifolium repens, (Jakobsen and Kristjansson, 1994), Thymus capitatus, (Petanidou and Smets, 1996), and Ziziphus spina-christi, (Nuru et al, 2012).…”
Section: Morphometric Valuesmentioning
confidence: 82%
“…Recently, Kim et al (2011) quantified the amount of nectar secreted per flower and per tree for Crataegus pinnatifida Bunge. The amount and dynamics of nectar secretion have been used, as well, to estimate the honey production potential of Ziziphus spina-christi (Nuru et al, 2012). In this general context, the aim of the current study was to determine the floral phenology, nectar secretion dynamics, and honey production potentials of the two, major, naturally growing Lavandula species (L. dentata, and L. pubescens) which are used as important sources of honey in regions of southwestern Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…Temperatures in the Mediterranean are expected to rise in the future more rapidly in summer than in any other season (Giorgi and Lionello, 2008 ; IPCC, 2013 ) and can surpass the optimal temperatures for nectar and sugar production. Mediterranean plants are generally well adapted to high temperatures and summer drought (Gratani and Varone, 2004 ; Petanidou, 2007 ; Miranda et al, 2011 ; Nuru et al, 2012 ). However, late-flowering species are already close to or beyond the optimal temperatures for photosynthesis (Larcher, 2000 ; Bussotti et al, 2014 ; Flexas et al, 2014 ), which determines the resources available for flower and nectar production (Southwick, 1984 ; Burquez and Corbet, 1998 ; Pacini et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%